Avaliação do estado nutricional, tolerância ao exercício e desempenho muscular em pacientes com doença pulmonar obstrutiva crônica - Silva, Karina Rabelo da (Universidade Federal de São Carlos, 2007)
Chronic obstructive pulmonary disease (COPD) is characterized by abnormal inflammation of the lungs in response to inhalation of noxious particles or toxic gases, especially cigarette smoke. COPD presents several systemic effects including nutritional depletion and musculoskeletal dysfunction that cause reduction in exercise tolerance. The aim of this study was evaluate the functional capacity and performance of the respiratory and peripheral muscles and relate them to nutritional status and FEV1. Methods: 12 patients with moderate-severe COPD (70±7 years, FEV1 52±17 % predict, BMI 23±4 kg/m2) and 7 healthy volunteers (69±8 years, FEV1 127±12% predict, BMI 27±3 kg/m2). All of them performed body composition analysis, measuring of maximal respiratory pressure (PImax and PEmax), a symptom-limited cardiopulmonary exercise test (TECR), evaluation of upper limbs force, peak torque and total work of the quadriceps femoral. Results: Patients with COPD had lower values of free-fat mass (FFM) index (18±1 versus 21±1 kg/m2, p≤0,05), maximal load in the TECR (60±20 versus 102±18 watts, p≤0,01), PImax (58±19 versus 87±21 cmH2O, p≤0,05), upper limb force (38±6 versus 47±5 kg, p≤0,05), peak torque (103±21 versus 138±18 N.m, p≤0,05) and total work of the quadriceps femoral (1570±395 versus 2333±568 J, p≤0,05) when compared with control group (test t-Student non-paired). It wasn t found correlation between FEV1 and the variables studied, and FFM index was correlated with the total work of the quadriceps (Pearson, r= 0,6290, p≤0,05). Conclusion: This results point to that patients with COPD show weakness of the inspiratory and peripheral muscles and a reduced functional capacity compared to a ix healthy group. Besides, it suggests that airflow limitation is not a good predictor to quantify nutritional and muscular debilities of patients with COPD.
Keywords: Fisioterapia respiratória; DPOC (Doença Pulmonar Obstrutiva Crônica); Sistema musculosquelético; Estado nutricional; Exercise intolerance; Muscle performance; COPD; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL